KONSEP HUKUM ISLAM TENTANG PELESTARIAN LINGKUNGAN HIDUP DALAM MENGATASI PENCEMARAN LINGKUNGAN - Wahyu Rasyid, Nurhaedah Hasan, Muthmainnah, Sartika (FAKULTAS HUKUM UM PAREPARE, 2022)
Cleanliness is part of Faith, the benchmark for seeing a believer is seen whether he is clean in terms of his environment and it is an obligation for every human being that we must live clean because it is part of belief. The main problem in this study is how the concept of Islamic law regarding environmental conservation in overcoming environmental pollution with sub-problems: 1) What is the concept of Islamic law regarding environmental conservation in overcoming environmental pollution. 2) What is the role of Islamic law regarding environmental conservation in overcoming environmental pollution. 3) How are the explanations of the Qur'an, hadith and laws regarding the concept of environmental conservation in overcoming environmental pollution. The purpose of this study is to 1) To find out the concept of Islamic law regarding environmental conservation in overcoming environmental pollution. 2) To find out the role of Islamic law on environmental conservation in overcoming environmental pollution. 3) To find out the explanation of the Qur'an, hadith and laws regarding the concept of environmental conservation in overcoming environmental pollution. This study uses a qualitative research type with an empirical normative approach. The source of the data used is to examine things that are theoretical by using secondary data, including the principles, rules, norms and legal rules contained in laws and regulations, studying books, and other documents that are closely related to this research. Based on this research, it shows that Islamic teachings are very appropriate in managing the environment, starting from commands, prohibitions, and recommendations that are fully listed in the holy book of Al-Quran and Hadith. In addition, Islamic teachings have great relevance and attention to the concept of ecology and the environment